The Factors Influencing Behavioural Intention Fintech Lending (Paylater) Among Generation Z Indonesian Muslims and Islamic Consumption Ethics Views - Siti Aisyah; M. Ikhsan Harahap; Nurbaiti Nurbaiti; Mustapa Khamal Rokan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This study seeks to investigate and analyze the factors that influence Generation Z’s use of fintech lending (paylater) in Jakarta, West Java, East Java, Central Java, and North Sumatra. This study employs a descriptive quantitative methodology and questionnaire distribution. The study employed purposive sampling. This study included 200 Generation Z respondents who have utilized fintech lending (paylater) as respondents. The method of data analysis employs Partial Least Square-Structural Equation Modeling (PLS-SEM) and SmartPLS version 3.2.9 software. The variables performance expectation, social influence, hedonic motivation, and habit have a positive and significant effect on behavioral intention, whereas effort expectation, facilitating conditions, and price value do not. In addition to testing the UTAUT 2 model, this research was conducted on Generation Z, where few research results are discussing the use of fintech lending (paylater). Generation Z is the generation that currently dominates the population in Indonesia and will be the next generation of Indonesians; therefore, it is essential to determine what factors play a role in encouraging the use of fintech lending (paylater) among Generation Z.AbstrakPenelitian ini tujuannya guna menyelidiki serta menganalisis faktor-faktor yang pengaruhi pemakaian fintech lending (paylater) generasi Z di Jakarta, Jawa Barat, Jawa Timur, Jawa Tengah, dan Sumatera Utara. Penelitian ini menggunakan metodologi kuantitatif deskriptif dan penyebaran kuesioner. Penelitian ini menggunakan purposive sampling. Penelitian ini melibatkan 200 responden generasi Z yang telah memanfaatkan fintech lending (paylater) sebagai responden. Metode analisis data memakai perangkat lunak PLS-SEM dan SmartPLS versi 3.2.9. Variabel ekspektasi kinerja, pengaruh sosial, motivasi hedonis, serta kebiasaan berpengaruh positif juga signifikan pada niat berperilaku, sedangkan ekspektasi upaya, kondisi fasilitasi, dan nilai harga tidak. Selain menguji model UTAUT 2, penelitian ini dilakukan pada generasi Z, dimana hasil penelitian yang membahas tentang penggunaan fintech lending (paylater) masih sedikit. Generasi Z merupakan generasi yang sekarang mendominasi jumlah penduduk di Indonesia dan akan menjadi generasi penerus bangsa Indonesia; Maka dari itu, penting agar tau faktor apa saja yang berperan untuk mendorong penggunaan fintech lending (paylater) di kalangan generasi Z.